EXPLORING THE RICH TAPESTRY OF ART AND CULTURE: THE TRADITIONAL ARTS AND CRAFTS OF THE DIDAYI TRIBE IN MALKANGIRI DISTRICT, ODISHA - Gudia, Jyotiranjan; Pattnaik, Tusarkant (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This article delves into the vibrant and diverse artistic heritage of the Didayi tribe, an indigenous community residing in Malkangiri District, Odisha, India. It explores the rich tapestry of traditional arts and crafts that define the cultural landscape of this unique tribe. From the intricate painting techniques that capture their mythological and everyday life, to the detailed craftsmanship in weaving, pottery, and bamboo work, the article provides an in-depth look at the Didayi tribe’s artistic practices. Additionally, it examines the significance of music and dance forms in their cultural rituals and community events. By highlighting the influences of the geographical regions of Khairaput, Karukonda, and Chitrakonda, the article illustrates how these factors shape and preserve the Didayi’s artistic expressions. Addressing the challenges faced in maintaining these traditions amidst modernization and globalization, it also underscores the ongoing efforts to preserve and promote this invaluable cultural heritage. Through this exploration, the article aims to foster a deeper appreciation for the Didayi tribe’s rich artistic legacy and the importance of cultural preservation.